Pengaruh Fraksi Volume Serat terhadap Peningkatan Kekuatan Impak Komposit Berpenguat Serat Nanas-Nanasan (Bromeliaceae) Kontinyu Searah dengan Matrik Unsaturated Polyester - Nur Rahman, Muhammad Budi; Suwanda, Totok (Semesta Teknika, 2010)
The objective of this research is to determine the effect of fiber volume fraction and alcali (5% NaOH solution) treatment on the impact strength and failure mode of continuous bromeliaceae fiber/BQTN 157 polyester composites. Specimens being tested were produced using press mold technique. Fiber volume fraction was varied from 20% to 40%, while the the soaking time of the alcali treatment was between 2 and 8 hours. Whilst the impact test was carried out in accordance with the ASTM D5941 standard, the micro-structures of the broken specimens were presented as photo macrographs. The result showed that failure energy was sharply increase, 0.22 J (69.23%), upto fiber volume fraction of 34,44%. Further increase of fiber content resulted in decreasing slope of the failure energy increase. The corresponding impact strength was found being 0,0046 J/mm2. The effect of soaking time of the alcali treatment on the failure energy and impact strength showed similar trend. Optimum result was obtained at 6 hours of soaking time, i.e. 0,27 J of failure energy and 0,0055 J/mm2 of impact strength. Eight hours of soaking time resulted in the damage of fiber surface leading to decrease of failure energy and impact srength of the resulted composites. Hinge break showing fiber pull out was observed in the failure surfaces of various fiber contents, with the increase of soaking time resulted in decrease of the amount of pulled-out fibers.